Generalized eruptive clear cell acanthomas - Thilo Gambichler; Ekaterina Heinzer; Ocko Kautz; Stefanie Boms (Wiley, 2023)
Abstract In most cases, clear cell acanthoma (CCA) is an uncommon solitary lesion with distinctive clinicopathological features. We report the case of an 80‐year‐old man with generalized asymptomatic skin lesions predominantly affecting his chest, abdomen and his legs. On dermoscopy, the lesions showed dotted vessels in a linear pearl‐like distribution ("pearl necklace") surrounded by a slightly whitish halo. Histopathology clearly confirmed the diagnosis of CCA. In conclusion, CCA being an uncommon solitary skin lesion may also appear in very rare cases as a generalized eruptive skin condition.